Globale Klimakonvention: Konflikt oder Kooperation zwischen Industrie- und Entwicklungsländern - Udo E. Simonis (Wissenschaftszentrum Berlin für Sozialforschung (WZB); Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1991)
The effort of negotiate a global Convention on climate change is one of mankind's great endeavours - and a challenge to economists and development planners. The inherent linkages between climate and the habitability of the earth are increasingly well recognized, and a Convention could help to ensure that conserving the environment and developing the economy in the future must go hand in hand. Due to growing environmental concern the United Nations General Assembly has set into motion an international negotiating process for a framework Convention on climate change. One the major tasks in these negotiations is how to share the duties in reducing climate relevant gases, particularly carbon dioxide (CO2), between the industrial and the developing countries. The results and proposals could be among the most far-reaching ever for socio-economic development, indeed for global security and survival itself. While the negotiations will be about climate and protection of the atmosphere, they will also be on fundamental global changes in energy policies, forestry, transport, technology, and on development pathways with low greenhouse gas emissions. Some of these aspects of a climate Convention, particularly the distributional options and consequences for the North-South relations, are addressed in this chapter.
Keywords: 330